Optimalisasi Pembinaan Bahasa Indonesia Melalui Media Pembelajaran Kentang Goreng - Ajeng Raya Vidia; Yayu Sopa Ikmali Rijki; Siti Elinda Nur Pebriantini; Yuni Ertinawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to optimize Indonesian language development, especially in correcting language errors in seventh-grade students through French fries as an interactive learning tool. This classroom action research was conducted in one cycle on 30 students of grade VII-E of SMP Negeri 12 Tasikmalaya in the 2025/2026 academic year. A qualitative approach with data collection techniques in the form of observation, sentence correction tests, interviews, and documentation was used in this study. The results showed that the use of French fries media with incorrect sentences in it can improve students' ability to identify and correct errors in spelling, grammar, and word choice. The percentage of completeness of sentence correction skills increased from 33.33% (pre-action) to 86.67% after the implementation of the action. This media can also increase student motivation and involvement in learning. It can be concluded that this French fries media is effective to be used as an aid in Indonesian language development that is fun and highly contextual.